Can a computer be an artist? Algorithms, evolution and the future of art - Boryczka, Urszula; Płosa, Tomasz (No Limits, 2025)
This article addresses the interdisciplinary issue of the relationship between evolution and art, in which algorithms, specifically evolutionary algorithms, play the role of a mediator. The starting point is a reflection on the inspirations drawn from biological evolution theory, which has found application in genetic algorithms, evolutionary programming, and other computational methods. The text shows how algorithms not only optimise solutions to technical problems but can also stimulate creative processes. It attempts to answer the question about the future of art in the era of artificial intelligence and the role of emotions or empathy in the digital creative process.